If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2(x + -1) = 4 + -3(x + 1) Reorder the terms: 3 + -2(-1 + x) = 4 + -3(x + 1) 3 + (-1 * -2 + x * -2) = 4 + -3(x + 1) 3 + (2 + -2x) = 4 + -3(x + 1) Combine like terms: 3 + 2 = 5 5 + -2x = 4 + -3(x + 1) Reorder the terms: 5 + -2x = 4 + -3(1 + x) 5 + -2x = 4 + (1 * -3 + x * -3) 5 + -2x = 4 + (-3 + -3x) Combine like terms: 4 + -3 = 1 5 + -2x = 1 + -3x Solving 5 + -2x = 1 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 5 + -2x + 3x = 1 + -3x + 3x Combine like terms: -2x + 3x = 1x 5 + 1x = 1 + -3x + 3x Combine like terms: -3x + 3x = 0 5 + 1x = 1 + 0 5 + 1x = 1 Add '-5' to each side of the equation. 5 + -5 + 1x = 1 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 1 + -5 1x = 1 + -5 Combine like terms: 1 + -5 = -4 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| -8m^4-12m^3-1871m^2+636m-457=0 | | 6-3(x+1)=2+3(2x+3) | | 3(3x-2)=2(2x-5) | | -16m^4-24m^3-3742m^2+1272m-934=0 | | (4-x^2)dy-4ydx=0 | | f(t)=sin(2t)*cos(2t) | | 4(x-3)+5=9 | | 3x-3+4=6 | | 10-(50+x)=15 | | 4x+24+5x+10=6x+6+5x+20 | | 5(1-3x)=-35 | | -2(5-5x)=-40 | | 11(x+1)=99 | | 7x-1=10x-10 | | 50-2x=90-4x | | 415-5x=390 | | 3x(1-x)=3(x-3) | | 6(3-4x)=-6 | | 4a+3b+6a-b= | | 5x(5x-1)-(5x+3)(5x-3)=x-3 | | 0.2ln(50.3)= | | (x-y)dx+(x+y)=0 | | 5x^3+10x^2+5x= | | 0.5x-33+x=42 | | 2x^2-10x+(k-5)=0 | | (x-y)DX+(x+y)day=0 | | Y=x+3ex | | 27-2,1/4=x | | (3x+4xy)dx+(2x+2y)dy=0 | | 2.4524X+1.3766(0.3256-X)=0.4637 | | (9D-12D+4)y=0 | | -2(3f-4)= |